2014
DOI: 10.5603/fhc.2013.0036
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between autophagy and proteasome protein degradation systems: possible implications for cancer therapy

Abstract: Abstract:The Ubiquitin-Proteasomes System (UPS) and autophagy, two main intracellular protein degradation pathways within the eukaryotic cells which were originally regarded as rather independent, seem to be very closely related. Proteasome inhibitors, including the multipathway inhibitor bortezomib, are drawing increased attention for their therapeutic potential in the treatment of chronic inflammation and cancer, especially tumours with a high degree of malignancy. The over-activation of autophagy induces ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 141 publications
1
46
0
Order By: Relevance
“…The proteasome system and autophagy machinery are regarded as the two major cellular protein degradation systems (3). It has been identified that proteasome inhibitor-induced autophagy is able to control endoplasmic reticulum stress and reduce cell death in cancer cells by activating the downstream inositol-requiring enzyme-1/c-Jun NH2-terminal kinase pathway (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteasome system and autophagy machinery are regarded as the two major cellular protein degradation systems (3). It has been identified that proteasome inhibitor-induced autophagy is able to control endoplasmic reticulum stress and reduce cell death in cancer cells by activating the downstream inositol-requiring enzyme-1/c-Jun NH2-terminal kinase pathway (18).…”
Section: Discussionmentioning
confidence: 99%
“…UPS-mediated proteolysis affects several different proteins through proteasome-mediated degradation, which is involved in the regulation of the cell cycle, apoptosis and cellular differentiation (2). Therefore, targeting this pathway using proteasome inhibitors may represent a novel approach for the treatment of cancer (3). A number of previous studies have demonstrated that proteasome inhibitors can induce tumor cell death via inhibiting proteasome activity (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Contrastingly, autophagy serves as an important mechanism to generate nutrients under cellular stress and may directly contribute to the cell survival following treatment with anticancer drugs. Autophagy may ultimately decrease the effect of anticancer therapies [13]. Therefore, autophagy appears to have a dual role in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There are 2 intracellular protein degradation pathways in eukaryotic cells: UPS and autophagy [13]. Inhibition of proteasomal activity or treatment with IR induces autophagy but not apoptosis in cancer cells [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been also proposed that, the synapsins may play a role in the formation and maintenance of synapses (synapsin I and II), synaptic vesicle fusion (synapsin I, II, and III) and its protein stabilisation (synapsin I and II), neurite elongation (synapsin I, II, and III) and neurogenesis (synapsin III) [24]. Lately, it has been postulated that synapsin cellular turnover is regulated by the ubiquitin-proteasome system (UPS) [6,14], the main system responsible for protein degradation in eukaryotic cells, which has currently become attractive research topic due to its involvement in neurodegenerative pathogenesis during aging, the inflammatory response, and the dynamics of tumour development [22,26].…”
Section: Introductionmentioning
confidence: 99%